An Unequal Partnership: The Privatisation of Information Technology in Ontario. (1st April 2015) - ,
Abstract : This paper presents a case study of the outsourcing of IT services between 1996 and 2003 by the Government of Ontario using a Public Private Partnership (P3) as an example of the commodification of public services including the impact on labour. It argues that three key features of the arrangement led to it becoming an 'unequal partnership.' First, ideological notions of a 'knowledge economy' and the techno-wizard status of independent IT workers were used by IT corporations to charge very high corporate rates for the time of outsourced IT staff, despite the fact that they were in fact undergoing a process of proletarianisation. Second, the P3 cost-benefit structure of shared costs and shared payments provided the framework for corporate partners to realise higher profits from investment in privatised state activities. Third, the explicit support of influential state and near-state actors undermined opposition to P3 projects.